Programa de actividades lúdicas y el nivel del logro área de Matemática en las estudiantes de una institución educativa, Trujillo - 2017 - Almirón García, Mirian Stefanny (2019)
The present report of investigation has like aim determine if the game program playful activities influences the level of achievement of Mathematics area in students an educational institution – Trujillo, 2017_x000D_ It worked with a sample of 60 students, 30 belonged to the experimental group and 30 to the control group. The used design is quasi experimental with experimental group and control. The problem solving capacity pre evaluated across an instrument.